2014
DOI: 10.1016/j.bbabio.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of the plastid terminal oxidase in photosynthetic electron transport

Abstract: The plastid terminal oxidase PTOX catalyzes the oxidation of plastoquinol (PQH2) coupled with the reduction of oxygen to water. In vivo PTOX is attached to the thylakoid membrane. PTOX is important for plastid development and carotenoid biosynthesis, and its role in photosynthesis is controversially discussed. To analyze PTOX activity in photosynthetic electron transport recombinant purified PTOX fused to the maltose-binding protein was added to photosystem II-enriched membrane fragments. These membrane fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…However, since the PSI-less mutant is highly sensitive to light (Shen et al, 1993), the contribution of Cox as an electron shuttle to oxygen is likely to be less efficient compared with PSI activity, or this could be a transient phenomenon. It is possible that, under specific conditions, Cox also produces reactive oxygen species via a mechanism similar to PTOX in plants (Heyno et al, 2009;Feilke et al, 2014;Yu et al, 2014), thereby generating oxidative damage to the cells. On the other hand, rapid light curve analysis demonstrated a slight but significant difference in Y(ND) values between Δcyd and Δcox/cyd cells under higher light intensities, indicating competition between PSI and Cox for electrons in the Δcyd mutant (Fig.…”
mentioning
confidence: 99%
“…However, since the PSI-less mutant is highly sensitive to light (Shen et al, 1993), the contribution of Cox as an electron shuttle to oxygen is likely to be less efficient compared with PSI activity, or this could be a transient phenomenon. It is possible that, under specific conditions, Cox also produces reactive oxygen species via a mechanism similar to PTOX in plants (Heyno et al, 2009;Feilke et al, 2014;Yu et al, 2014), thereby generating oxidative damage to the cells. On the other hand, rapid light curve analysis demonstrated a slight but significant difference in Y(ND) values between Δcyd and Δcox/cyd cells under higher light intensities, indicating competition between PSI and Cox for electrons in the Δcyd mutant (Fig.…”
mentioning
confidence: 99%
“…When PTOX is overexpressed it can generate O 2 •− in the light (Heyno et al ), and such process was also shown in experiments with isolated enzyme (Feilke et al , Yu et al ). This may be the intrinsic feature of the enzyme, which performs the four‐electron reduction of the molecule O 2 through formation of the peroxide intermediates and can generate ROS in a side reaction with a rate that depends on the quinol concentration and pH value.…”
Section: Biochemical Pathways Influencing the Redox State Of The Pq Poolmentioning
confidence: 78%
“…In the presence of DCMU, an inhibitor that binds to the Q B binding pocket, no difference between Cr‐PTOX1 and wild‐type was any longer observed (Figure a,b). Addition of the inhibitor octylgallate also abolished the difference between thylakoids from Cr‐PTOX1 plants and wild‐type (not shown, but see Feilke et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…We suppose that both, the pH value and the ion concentration, are crucial for the attachment of PTOX to the membrane. According to reconstitution experiments using recombinant Os‐PTOX fused with the maltose binding protein, a more alkaline pH and the presence of sodium in comparison to calcium increased the attachment of PTOX to the membrane (Feilke et al ., ). In the present state, we do not know if the association of PTOX with the membrane changes depending on the pH value or ion concentrations, if the interaction of PTOX with a putative partner protein is interrupted or if alterations of the pH induce a conformational shift in the PTOX protein structure that leads to a dissociation of the protein from the membrane.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation